Revised European Society of Endocrinology Clinical Practice Guideline for the management of aggressive pituitary tumours and pituitary carcinomas - Raverot, Gerald; Burman, Pia; Abreu, Ana Paula; Heaney, Anthony P.; Van Hulsteijn, Leonie; Lin, Andrew L.; Marcus, Hani; McCormack, Ann; Minniti, Giuseppe; Petersenn, Stephan; Popovic, Vera; Theodoropoulou, Marily; et al. (European Journal of Endocrinology, 2025)
Pituitary tumours, originating from endocrine cells of the anterior pituitary, are quite common, and in most cases well-controlled by surgery or medical treatment. However, a small subset of pituitary tumours presents with multiple local recurrences or tumour progression despite combined surgical, medical or radiotherapeutic treatment. These are known as aggressive pituitary tumours (APT); also called aggressive pituitary neuroendocrine tumours (PitNETs); or, in the rare case of metastases, pituitary carcinomas (PC) or metastatic PitNETs. Early identification of APT is challenging but is of major clinical importance as they are associated with an increased morbidity and mortality even in the absence of metastases. Here, we provide a revision of the first international, interdisciplinary European Society of Endocrinology (ESE) clinical practice guideline on APTs and PC (2018). Since publication of the 2018 guideline, results from the second ESE survey on APT and PC were published, and more data on APT treatment, including temozolomide, immune checkpoint inhibitors and bevacizumab, emerged. These data are reviewed in this guideline and translated into a practical algorithm to guide APT and PC management. Furthermore, standardized reporting of imaging and histopathological investigations of these tumours is proposed, and the role of molecular analysis is discussed. Last, a section is dedicated to special circumstances such as APT in pregnancy.
Publisher Copyright: © 2025 The Author(s). Published by Oxford University Press on behalf of European Society of Endocrinology.
Keywords: aggressive pituitary tumour-Pituitary carcinoma; pituitary adenoma; prognosis; therapy